Typhoon Fung-wong (2008) induced heavy metals secondary pollution in Quanzhou Bay, southeast of China. (March 2021) - Lin, Yunpeng; Li, Yunhai; Wang, Liang; Zheng, Binxin; Yin, Xijie; Xu, Yonghang
Abstract: The concentrations of Cr, Ni, Cu, Zn, As, Cd, Pb, and Al in suspended particles were measured, and temperature, salinity, flow velocity and direction during a tidal cycle were observed before and after Typhoon Fung-wong at six stations in Quanzhou Bay, respectively. The comparison results show that, after the typhoon, the salinity in Quanzhou Bay decreased, whereas the concentrations of heavy metals increased by a factor of between 2 and 10, and the high heavy metal concentration corresponded to the low value of ratio between heavy metals and Al (HMs/Al), suggesting that these increased heavy metals were mainly from natural sources. Instantaneous unit width flux calculations for heavy metals at different stations indicate that sediments are an important source of heavy metals in suspended particles under the influence of typhoon, which has significantly contribution to understanding the impact of typhoons on the heavy metal pollution in the coastal area. Graphical abstract: Unlabelled Image Highlights: Heavy metal concentrations decreased from the estuary to the outer bay. Dynamics of typhoon influenced hydrodynamic environment in the bay. Heavy metal flux input by Jinjiang River increased after typhoon. Typhoon caused heavy metals to resuspend and induced secondary pollution.